Benzocaine and eugenol as anesthetics for Brycon hilarii - doi: 10.4025/actascianimsci.v35i2.16644 - Bruno Matucita Fabiani; Wilson Rogério Boscolo; Aldi Feiden; Odair Diemer; Fábio Bittencourt; Dacley Hertes Neu (Acta Scientiarum. Animal Sciences, 2012)
Anesthetic products are frequently employed during fish handling practices; however, the correctdoses of the various chemicals for different species are still unknown. This study determined the idealconcentrations of benzocaine and eugenol as anesthetics used in Brycon hilarii juveniles. The fish were acquiredfrom a commercial fish farm located in western Paraná state, Brazil, totaling 104 juveniles, with average bodyweight and length of 50.04 ± 20.80 g and 16.30 ± 12.32 cm respectively. The study was carried out at theAquiculture Laboratory from the Aquaculture Management Study Group - GEMAq at the West Parana StateUniversity. Five benzocaine concentrations (50.0, 100.0, 150.0, 200.0 and 250.0 mg L-1) and seven eugenolconcentrations (50.0, 100.0, 150.0, 200.0, 250.0, 300.0 and 350 mg L-1) were evaluated in order to assess theinduction time to anesthesia. The fish were transferred to anesthetic-free tanks to recover, and the time needed toreturn to normal activity was recorded. The best results were observed with the benzocaine dose of 100 mg L-1and the eugenol dose between 100 and 150 mg L-1.